Lao People's Democratic Republic : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2000)
This report discusses major developments in the Lao People's Democratic Republic (PDR), and updates the statistical tables on recent economic developments and provides an overview of the real sector. Factors that have limited revenue collections and developments in the monetary and financial sectors have been presented. The paper discusses the weakness of monetary policy as well as the financial sector and recent efforts to reform the banking system. Foreign direct investment and foreign exchange regime in Lao PDR have been examined.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet